The long non-coding RNA Snhg15 protects the heart after myocardial infarction - Shumliakivska, Mariana; Fischer, Ariane; Muhly-Reinholz, Marion; Leonard, Vincent Elvin; Rasper, Tina; Aslan, Galip S.; Manavski, Yosif; Wagner, Julian U. G.; Meder, Benjamin; Hille, Susanne S.; Müller, Oliver J.; Luxán, Guillermo; et al. (Journal of molecular and cellular cardiology, 2026)
Cardiomyocytes are postmitotic cells that do not proliferate in the heart. In order to maintain the structural integrity of the heart, cardiomyocyte loss due to cell death after myocardial infarction is compensated with a non-contractile fibrotic scar that compromises cardiac function. Here, we have combined heart failure transcriptomics with in vitro assays to determine the molecular mechanisms that govern cell death in heart failure. Our data identified the reduced gene expression of the long non-coding RNA (lncRNA) small nucleolar RNA host gene 15 (Snhg15) as a hallmark of ischemic and dilated heart failure. Furthermore, loss-of-function studies in HL-1-cardiomyocyte-like cells revealed that Snhg15 depletion induces nucleolar disruption and cell death in a p53-dependent mechanism. Finally, adeno-associated virus delivery of Snhg15 prior to a myocardial infarction partially protected cardiac function in the acute and chronic phases after myocardial infarction. In conclusion, our studies identify Snhg15 as a regulator of cardiomyocyte cell death in the context of heart failure and suggest that delivery of the lncRNA may represent a potential therapeutic tool to reduce cardiomyocyte death.
Online verfügbar 27 October 2025, Version des Artikels 13 November 2025
Gesehen am 02.03.2026